If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + 3y + 7 = 32 Reorder the terms: 7 + 2y + 3y = 32 Combine like terms: 2y + 3y = 5y 7 + 5y = 32 Solving 7 + 5y = 32 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 5y = 32 + -7 Combine like terms: 7 + -7 = 0 0 + 5y = 32 + -7 5y = 32 + -7 Combine like terms: 32 + -7 = 25 5y = 25 Divide each side by '5'. y = 5 Simplifying y = 5
| 10m+6n=-2 | | (x/8)+2=(x/8) | | -6y+60=18 | | 3n-28=2 | | 9x-7=24x+3 | | 5n=13-3m+1 | | n/-6=-25 | | 4y+3=7y+12 | | 18x+15=9x+42 | | n/-8=14 | | 7f-20=50 | | 27-9t=18 | | 3f+3=6 | | 9-4x=-x+18 | | 11/24(9/4) | | .60x+.15(190)=.30(45) | | 11x-4x=28 | | 0.84x=0.4y+0.6z | | x/5-6=-11 | | 1/3+1/8 | | 5/n+5+5/n-3 | | 7x-12=5x+12 | | x/(-12)=-36 | | 1/3^-1/5 | | (7x)-24=5x | | (4m+2)(3m+9)=0 | | 200-215/3 | | 9a+5=-3a-1 | | (8x^2+6x-3)-(-2x^2+9x-17)= | | 5x^3=625 | | -5n=5n+6 | | 39=(w-2)*(3w-2) |